Metabolic regulation of immunological synergism between Toll-like receptor and Fc-receptor signalling - Kuijper, Elsa; Everts, Bart (Student Undergraduate Research E-journal!, 2016)
Macrophages and dendritic cells (DCs), critical immune regulators, demonstrate synergistic cytokine production upon co-stimulation with Fc-receptor and Toll-like receptor (TLR) ligands. Since cytokine production upon TLR-triggering depends on glycolysis, this research investigated whether cytokine synergism also requires glycolysis. This was analysed in (co)-stimulated human macrophages, monocyte-derived DCs (MODCs) and retinoic acid DCs (RADCs). We showed that co-stimulation additionally enhances glycolysis compared to TLR-stimulation alone. However, synergism depended on glycolysis in RADCs only, whereas macrophages and MODCs showed synergistic gene expression, indicating translational and transcriptional regulation respectively. Elucidating these mechanisms could improve clinical manipulation of immune responses.